2016
DOI: 10.1007/s00787-016-0834-5
|View full text |Cite
|
Sign up to set email alerts
|

Psychological treatments for depression in pre-adolescent children (12 years and younger): systematic review and meta-analysis of randomised controlled trials

Abstract: (250 words)Objective: To evaluate the efficacy of psychological treatments for depression in pre-adolescent children, a disorder affecting 1-2% of children in this age-range. Design:Systematic review of studies of psychological interventions to treat depressive disorder in preadolescent children (aged up to 12 years old). The primary outcome was level of depressive symptoms.Data Sources: Studies were found using Medline, PsycINFO, EMBASE and Web of Knowledge databases and selected on several criteria.Eligibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 22 publications
4
14
0
2
Order By: Relevance
“…Similar results were found concerning depression outcomes (overall g = 0.50, p < .001). This effect is similar to pooled effect sizes found in recent meta-analyses of disorderspecifi c CBT for depression in children (Forti-Buratti, Saikia, Wilkinson, & Ramchandani, 2016), although the small number of studies included in the meta-analysis makes this result diffi cult to interpret meaningfully. Although the evidence is still inconclusive, it appears that the effi cacy of transdiagnostic CBT protocols applied to children and/or adolescents is somewhat lower than the effi cacy of the protocols applied to adults.…”
Section: Summary Of Evidencesupporting
confidence: 82%
“…Similar results were found concerning depression outcomes (overall g = 0.50, p < .001). This effect is similar to pooled effect sizes found in recent meta-analyses of disorderspecifi c CBT for depression in children (Forti-Buratti, Saikia, Wilkinson, & Ramchandani, 2016), although the small number of studies included in the meta-analysis makes this result diffi cult to interpret meaningfully. Although the evidence is still inconclusive, it appears that the effi cacy of transdiagnostic CBT protocols applied to children and/or adolescents is somewhat lower than the effi cacy of the protocols applied to adults.…”
Section: Summary Of Evidencesupporting
confidence: 82%
“…16 The effectiveness of Internet-based psychotherapeutic interventions in children/adolescents has also been explored. One meta-analysis found no significant benefit to Internetbased interventions in 7-to 25-year-olds on depression symptoms (although anxiety was reduced) compared with waitlist controls.…”
Section: Is Psychotherapy An Effective Treatment For Depressed Childrmentioning
confidence: 99%
“…Further systematic reviews have found certain types of family therapy to be effective in treating externalising disorders (von Sydow et al, 2013) and in improving functioning and reducing hospitalisation (Shepperd et al, 2009) in child and youth mental health. Despite varied evidence to support the efficacy of family therapy for depression in children and adolescents (Forti-Buratti, Saikia, Wilkinson, & Ramchandani, 2016;Hazell, 2009), family therapy has been cited as an effective (Carr, 2008) and clinically useful (Paz Pruitt, 2007) treatment in reviews of treatments for young people with depression. Various family therapy models have been shown to be effective in reducing mental health symptomatology and improving family function for children and youth with eating disorders, and those with externalising mental health problems (Jewell et al, 2016;Lock & Gowers, 2009;Porter & Nuntavisit, 2016).…”
Section: Discussionmentioning
confidence: 99%